The masked puppet as pattern of semiotics and aesthetics - Alexander V. Markov; Oksana A. Shtayn (Семиотические исследования)
The notion of the masked puppet allows us to bridge the idea of the mask and puppet theater, and thus the idea of social strategy, with the intrinsic imaginative configurations of things, the unexpected inspiration that things provide. This article explores the possibility of reviving some of the functions of the archaic mask, drawing on Kwasi Wiredu’s African philosophy, Graham Harman’s object-oriented ontology, and a wide range of data from contemporary genre films, animated films, and art installations. The archaic mask represents a symbiotic principle as an alternative to the mimetic principle, and the various ways in which the puppet and mask are used simultaneously relate the mimetic principle to everyday life, while the symbiotic principle becomes a principle of innovative practical action. The paper considers the different variants of the masked puppet: the pantomime in its opposition to the templates of theater art; the automaton, as a variant of the mechanism that removes and puts on the mask in the course of imitating human functions; and finally, horror films, where the most human features, such as eyes, act as the mask of the puppet. Setting the various phenomena of cinema, animation, literature, and applied art in the same row shows that the masked puppet is not a topos or a technique that reinforces dramatic expectations or actualizes modes of affectivity, but a means of creating a new mode of affectivity in the here and now, which is demanded by applied aesthetics. The poetic examples confirm that such a mode of affectivity can be triggered not by a situation of conflict, but by the shared experience of encountering a work of art or craft. This mode implicates the aesthetics of fear and transfiguration that has found a place in horror. But it is also a mode that allows us to plan the elaboration of public symbols that are accepted by the collective as legitimate and necessary for its self-awareness.